Annual population dynamics of the small harpacticoid copepod Microsetella norvegica in a high latitude fjord (Balsfjord, Northern Norway) - Antonsen, Maria Terese (UiT Norges arktiske universitet, 2014)
Annual population dynamics and vertical distribution of the small (< 0.6 mm) hapacticoid copepod, Microsetella norvegica, was investigated through monthly sampling at station Svartnes in Balsfjord, Northern Norway from May 2013 to June 2014. M. norvegica is a pelagic particle feeder, and distributed from temperate waters to sub-arctic fjords, but frequently underestimated because of its small size. The species is therefore often overlooked and its biology poorly understood. In order to sample all stages of M. norvegica, from nauplii to adult appropriately, we used both a WP-2 net with 90 µm mesh size (175-50 and 50-0 m), and a 20 L Go-Flo water bottle (5, 20, and 50 m depth). Nauplii and copepodite stages from CI to adult were identified to determine total abundance, population structure, vertical and seasonal distribution. There were great differences in abundances and stage distribution dependent on sampling method. The Go-Flo bottle sampled all stages, from nauplii to adult stages, while the WP-2 net collected mostly adult stages. The discrepancy in sampling efficiency between the two gears is also clearly reflected when comparing the abundances. In June 2014 the total maximum abundance of M. norvegica, when integrating Go-Flo from 50-0 m, was 7.8 x 106 ind. m-2. When sampling with WP-2 we found a total maximum abundance of 1.2 x 106 ind. m-2. Minimum abundances of M. norvegica were found in January 2014. Females carrying egg-sac were observed in April to June and in August. Females carrying egg-sac peaked in June, with a total abundance of 754 270 ind. m-2, when integrating Go-Flo from 0 to 50 m. Also, total abundance of females and egg-sacs in the upper 50 m was used to calculate the egg-sac:female ratio, where we found the highest ratio at 1.6 in May. Nauplii and small copepodite stages peaked in the upper 50 m in spring and summer, suggesting that their main reproductive period takes place in May and June. The older copepodite stages from CIV to adults dominated in winter from October to March. To ...